Super capacitor composite electrode material, preparation method and electrode system
By compositeing MXene nanosheets with Co-MOF, NiCo-LDH and Co9S8 materials, MXene@NiCo-LDH/Co9S8 composite electrode material is formed, the problems of low energy density and insufficient cycle stability of supercapacitor electrode materials are solved, and high capacitance and good cycle stability are achieved.
Patent Information
- Application Number
- CN202411974522.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-09-02
- Filing Date
- 2024-12-31
- Publication Date
- 2025-05-09
AI Technical Summary
The supercapacitor electrode material has low energy density and insufficient cycle stability, which cannot meet the needs of different energy storage systems.
A preparation method is adopted to obtain MXene nanosheets by etching Ti3AlC2 and composite them with materials such as Co-MOF, NiCo-LDH and Co9S8 to form MXene@NiCo-LDH/Co9S8 composite electrode material to improve its conductivity and cyclic stability.
The capacitance and cyclic stability of the supercapacitor electrode material are significantly improved, and are better than the electrode material performance in the prior art.
Smart Images

Figure CN119964996A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of supercapacitor electrode material preparation, and in particular to a supercapacitor composite electrode material, a preparation method and an electrode system. Background Art
[0002] With the adjustment of the global energy structure and the rapid development of renewable energy technology, supercapacitors, as a high-performance energy storage device, play an important role in solving energy storage and environmental problems. Supercapacitors have the advantages of high power density, fast charge and discharge, long cycle life, and good stability. They have broad application prospects in electric vehicles, hybrid vehicles, rail transportation and other fields, and are considered to be one of the most promising energy storage devices of the next generation.
[0003] However, compared with batteries, supercapacitor electrode materials have low energy density and insufficient cycle stability, and their limited energy density hinders their commercialization. In order to meet the needs of different energy storage systems, the required electrode materials should have high conductivity, high ion transport rate and large contact area. At present, supercapacitor electrode materials have relatively low energy density and insufficient cycle stability. To solve this defect, unlike conventional capacitors, we are committed to integrating the characteristics of battery types and supercapacitor electrodes into one device through layered assembly, so as to improve the energy density of electrode materials, as well as fast charging and discharging capabilities and cycle stability.
[0004] Based on the current problems of low energy density, insufficient cycle stability and energy density of supercapacitors that cannot meet the application requirements of different energy storage systems, it is necessary for the applicant to further research and expand the corresponding electrode materials to develop a new product that can solve these problems to a certain extent. Summary of the invention
[0005] The purpose of the present invention is to solve the above-mentioned defects and problems of electrode materials for supercapacitors, and to provide a method for preparing a supercapacitor composite electrode material with rich pores, high charge transfer capacity and double-layer structure, and to prepare a composite electrode material with excellent performance by this preparation method, which has abundant pores and can significantly promote the diffusion of electrolyte ions and improve the charge transfer capacity. At the same time, a supercapacitor electrode system with excellent performance is prepared by using this composite electrode material.
[0006] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a supercapacitor composite electrode material, the preparation method specifically comprising the following steps: (1) Preparation of MXene dispersion: Ti3AlC2 was added to a hydrochloric acid solution of lithium fluoride, stirred at 30-50°C for 22-26 hours, centrifuged and washed, and then the centrifuged product was vacuum dried at 50-70°C for 10-14 hours. Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion; (2) Preparation of Co-MOF: First, prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, then mix and stir the two solutions evenly, react for 22-26 hours, and finally centrifuge and dry the obtained product to obtain the polyhedral precursor Co-MOF; (3) Preparation of MXene@Co-MOF composite membrane: adding the Co-MOF prepared in step (2) to the MXene dispersion prepared in step (1), stirring evenly, and preparing a MXene@Co-MOF composite membrane by vacuum filtration; (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a mixed solvent of deionized water and ethanol to prepare a solution, and then the MXene@Co-MOF composite membrane prepared in step (3) was immersed in the solution and kept at room temperature for 22 to 26 hours to obtain a MXene@NiCo-LDH membrane; (5) Preparation of MXene@NiCo-LDH / Co9S8: Prepare an ethanol solution of thioacetamide, and then immerse the MXene@NiCo-LDH film prepared in step (4) in the solution and react at 110-130°C for 1-3h to obtain MXene@NiCoLDH / Co9S8, which is the product supercapacitor composite electrode material.
[0007] In the above-mentioned preparation process of the present invention Step (1) Ti3AlC2 in lithium fluoride is etched by hydrochloric acid. The aluminum (Al) layer in Ti3AlC2 is etched by the hydrochloric acid and lithium fluoride to obtain nanosheets with a layered structure, and finally a layered Ti3C2T X MXene nanosheets; Step (2) is mainly through Co 2+ The ions react with 2-methylimidazole molecules to form a metal-organic framework material with a three-dimensional network structure, and finally a Co-MOF polyhedral precursor is obtained; Step (3) Stirring the two to mix them evenly and form a mixture of MXene and Co-MOF. In this process, there is a physical adsorption effect between the MXene nanosheets and the Co-MOF particles, and a composite structure is initially formed. The solvent in the solution is rapidly evaporated by vacuum filtration, and the MXene nanosheets and Co-MOF particles are retained on the filter membrane to form a dense composite membrane MXene@Co-MOF. Step (4), mainly through Ni 2+ The NiCo-LDH layer is completely covered on the surface of the MXene@Co-MOF composite film to form a MXene@NiCo-LDH film. The preparation process of step (5) is a process of converting part of the metal ions in the MXene@NiCo-LDH film into a sulfide phase through a sulfidation reaction. It is a product of a composite material loaded on MXene. NiCo-LDH also has certain capacitance performance. Co9S8, as a sulfide, has a high theoretical specific capacity and can provide a high energy storage capacity for the composite material, further enhancing the energy density of the composite material. The final product is a MXene@NiCoLDH / Co9S8 composite material, which combines the high conductivity of MXene, the layered structure of LDH and the high theoretical capacitance performance of Co9S8; the MXene@NiCoLDH / Co9S8 composite electrode material has high conductivity and excellent cycle stability, and is an excellent supercapacitor electrode material.
[0008] Preferably, in the hydrochloric acid solution of lithium fluoride in step (1), the mass concentration of lithium fluoride is 10-30 mg / ml.
[0009] Preferably, in step (1), the amount of Ti3AlC2 added to every 100 ml of lithium fluoride hydrochloric acid solution is 1.0-3.0 g.
[0010] Preferably, the concentration of the MXene dispersion in step (1) is 4-5 mg / ml.
[0011] Preferably, in step (2), the two methanol solutions are mixed in a volume ratio of 1:1, and in every 20 ml of methanol, the amount of Co(NO3)2·6H2O is 0.7-1.1 g, and the amount of 2-methylimidazole is 1.1-2.1 g.
[0012] Preferably, in step (3), the amount of Co-MOF used in every 10 ml of MXene dispersion is 40-60 mg.
[0013] Preferably, in step (4), the ratio of deionized water to ethanol is 1:2, and the amount of Ni(NO3)2·6H2O used in every 30 ml of mixed solvent is 10-30 mg.
[0014] Preferably, the amount of thioacetamide used in the ethanol solution of thioacetamide in step (5) is 10-20 mg per 10 ml of ethanol.
[0015] A supercapacitor composite electrode material is prepared by the above-mentioned preparation method.
[0016] A supercapacitor electrode system uses the composite electrode material as the positive electrode; the negative electrode is prepared by mixing activated carbon, acetylene black and polyvinylidene fluoride, then mixing with ethanol as a solvent and smearing on a foamed Ni sheet.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The composite electrode material prepared by the preparation method of the present invention has excellent supercapacitor performance and cycle stability when used for supercapacitor electrodes; the capacitance it possesses is much higher than the capacitance possessed by electrode materials commonly used in current supercapacitors. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 It is a preparation flow chart of the present invention.
[0019] Figure 2 The SEM images of the products at different stages in the process of preparing the composite electrode material of the present invention, the EDS images of the composite material, and the TEM and HRTEM images; in: (a, b) are SEM images after processing in step (3); (c, d) are SEM images after processing in step (4); (e, f) are SEM images of the composite electrode material finally prepared in step (5); (g) is an energy dispersive x-ray spectroscopy (EDS) mapping image of the composite electrode material finally prepared in step (5); (hi) are transmission electron microscopy (TEM) and HRTEM images of the composite electrode material finally prepared in step (5).
[0020] Figure 3 This is a diagram showing the advantages of the components of the composite electrode material of the present invention: in: (a) CV curve of MXene@NiCo-LDH / Co9S8; (b) The linear relationship between the current logarithm (i) and the scan rate logarithm (v) of MXene@NiCo-LDH / Co9S8; (ce)MXene@NiCo-LDH / Co9S8 electrode at 2 mV -1 , 3.5 mV -1 and 5 mV -1 The distributed capacitance contribution under (f) Capacitance control and diffusion control percentage of MXene@NiCo-LDH / Co9S8 electrode; (hj) CV curves of MXene@NiCo-LDH and MXene@NiCo-LDH / Co9S8, and the linear fitting curves of scan rate and capacitance current.
[0021] Figure 4 This is a performance characterization diagram of the composite electrode material prepared in the present invention (Example 2): in: (a) Cyclic voltammetry (CV) curves of MXene@Co-MOF, MXene@NiCo-LDH and MXene@NiCoLDH / Co9S8 at different voltages. (b) Current density is 1 A -1 When , the GCD curves of the above three samples; (cd) CV and GCD curves of MXene@NiCo-LDH / Co9S8 under different test conditions; (e) Weight voltage of MXene@NiCo-LDH / Co9S8; (f) Nyquist plots of the above three samples.
[0022] Figure 5 This is the electrochemical performance test diagram of MXene@NiCo-LDH / Co9S8 / / AC supercapacitor: (a) Schematic diagram of MXene@NiCo-LDH / Co9S8 / / AC device; (b) CV curves of MXene@NiCo-LDH / Co9S8 / / AC positive and negative electrodes; (cd) CV curves of ASC of the device at different voltage windows and scan rates; (ef) GCD curves and calculated specific capacity at different current densities.
[0023] Figure 6 The test result diagram of Comparative Examples 1 and 2 of the present invention; in: (ab) CV and GCD curves of MXene@Co-MOF. (cd) CV and GCD curves of MXene@NiCo-LDH. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] like Figure 1 As shown, the present invention provides a method for preparing a supercapacitor composite electrode material, such as Figure 1 As shown, this is a flow chart of the present invention. The specific steps are as follows: A method for preparing a supercapacitor composite electrode material, the preparation method specifically comprising the following steps: (1) Preparation of MXene dispersion: Ti3AlC2 was added to a hydrochloric acid solution of lithium fluoride, stirred at 30-50°C for 22-26 hours, centrifuged and washed, and then the centrifuge was vacuum dried at 50-70°C for 10-14 hours. Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion; in the hydrochloric acid solution of lithium fluoride, the mass concentration of lithium fluoride is 10-30 mg / ml; the amount of Ti3AlC2 added to every 100 ml of the hydrochloric acid solution of lithium fluoride is 1.0-3.0 g; the concentration of the MXene dispersion is 4-5 mg / ml; (2) Preparation of Co-MOF: First, prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, then mix and stir the two solutions evenly, react for 22-26 hours, and finally centrifuge and dry the resulting product to obtain the polyhedral precursor Co-MOF; the two methanol solutions are mixed in a volume ratio of 1:1, and the amount of Co(NO3)2·6H2O is 0.7-1.1 g, and the amount of 2-methylimidazole is 1.1-2.1 g per 20 ml of methanol; (3) Preparation of MXene@Co-MOF composite membrane: Add the Co-MOF prepared in step (2) to the MXene dispersion prepared in step (1), stir evenly, and prepare the MXene@Co-MOF composite membrane by vacuum filtration; the amount of Co-MOF in every 10 ml of MXene dispersion is 40-60 mg; (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a mixed solvent of deionized water and ethanol to prepare a solution, and then the MXene@Co-MOF composite membrane prepared in step (3) was immersed in the solution and kept at room temperature for 22 to 26 hours to obtain a MXene@NiCo-LDH membrane; the ratio of deionized water to ethanol was 1:2, and the amount of Ni(NO3)2·6H2O was 10 to 30 mg per 30 ml of the mixed solvent; (5) Preparation of MXene@NiCo-LDH / Co9S8: Prepare an ethanol solution of thioacetamide, then immerse the MXene@NiCo-LDH membrane prepared in step (4) in the solution, and react at 110-130°C for 1-3h to obtain MXene@NiCoLDH / Co9S8, which is the product supercapacitor composite electrode material. The ethanol solution of thioacetamide is 10-20 mg per 10 ml of ethanol.
[0027] The following are specific examples.
[0028] Embodiment 1: (1) Preparation of MXene dispersion: 1.0 g Ti3AlC2 powder was slowly added to 1.5 g lithium fluoride hydrochloric acid solution, stirred at 30 °C for 22 h, centrifuged and washed, and then the centrifuge was vacuum dried at 50 °C for 10 h. Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion, wherein the concentration of MXene is 4 mg / mL; (2) Preparation of Co-MOF: Prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, 20 ml of methanol, 0.6 g of Co(NO3)2·6H2O, and 1.2 g of 2-methylimidazole; Then, the two solutions were mixed and stirred evenly. After reacting for 22 hours, the obtained product was finally centrifuged and dried to obtain the polyhedral precursor Co-MOF for later use; (3) Preparation of MXene@Co-MOF composite membrane: First, the Co-MOF prepared in step (2) is added to the MXene dispersion prepared in step (1), and stirred evenly. The amount of Co-MOF used is 40 mg. The MXene@Co-MOF composite membrane is obtained by vacuum filtration and set aside. (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a solvent of deionized water and ethanol to prepare a solution. In 10 mL of deionized water and 20 mL of ethanol solvent, the amount of Ni(NO3)2·6H2O was 10 mg. Then, the MXene@Co-MOF composite membrane prepared in step (3) was immersed therein and kept at room temperature for 22 h to obtain a MXene@NiCo-LDH composite membrane. (5) Preparation of MXene@NiCo-LDH / Co9S8: prepare an ethanol solution of thioacetamide, 10 mL of ethanol, and 10 mg of thioacetamide, then immerse the MXene@NiCo-LDH film prepared in step (4) in the solution, and react at 110°C for 1 h to obtain MXene@NiCo-LDH / Co9S8, which is the product supercapacitor composite electrode material; Then, the electrode is prepared using the above electrode material; Finally, Hg / HgO and Pt electrodes were used as reference electrodes, and the obtained composite electrode material was used as the positive electrode. Activated carbon, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and then mixed with ethanol as a solvent and applied on a foamed Ni sheet to prepare a negative electrode.
[0029] Embodiment 2: (1) Preparation of MXene dispersion: 2.0 g Ti3AlC2 powder was slowly added to 2.0 g lithium fluoride hydrochloric acid solution, stirred at 40 °C for 24 h, centrifuged and washed. The centrifuge was then vacuum dried at 60 °C for 12 h, and Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion, the concentration of MXene is 4.5 mg / mL; (2) Preparation of Co-MOF: Prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, 20 ml of methanol, 0.9 g of Co(NO3)2·6H2O, and 1.6 g of 2-methylimidazole; Then, the two solutions were mixed and stirred evenly. After reacting for 24 hours, the obtained product was finally centrifuged and dried to obtain the polyhedral precursor Co-MOF for later use; (3) Preparation of MXene@Co-MOF composite membrane: First, the Co-MOF prepared in step (2) is added to the MXene dispersion prepared in step (1), and stirred evenly. The amount of Co-MOF used is 50 mg. The MXene@Co-MOF composite membrane is obtained by vacuum filtration and set aside. Figure 2 (a, b) are SEM images of MXene@Co-MOF composite films; Co-MOFs with polyhedral structures are embedded in the MXene layer; (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a solvent of deionized water and ethanol to prepare a solution. The amount of Ni(NO3)2·6H2O was 20 mg in 10 mL of deionized water and 20 mL of ethanol solvent. Then, the MXene@Co-MOF composite membrane prepared in step (3) was immersed in it and kept at room temperature for 24 h to obtain a MXene@NiCo-LDH composite membrane. Figure 2 (c, d) are SEM images of MXene@NiCo-LDH; the solid polyhedral structure is transformed into a hollow structure; (5) Preparation of MXene@NiCo-LDH / Co9S8: prepare an ethanol solution of thioacetamide, 10 mL of ethanol, and 15 mg of thioacetamide, then immerse the MXene@NiCo-LDH film prepared in step (4) in the solution, and react at 120°C for 2 h to obtain MXene@NiCo-LDH / Co9S8, which is the product supercapacitor composite electrode material; Figure 2 (e, f) are SEM images of MXene@NiCo-LDH / Co9S8, which are the overall structure diagram of MXene@NiCo-LDH / Co9S8 film and the element distribution diagram of MXene@NiCo-LDH / Co9S8; (g) is the energy dispersive x-ray spectroscopy (EDS) mapping image of MXene@NiCo-LDH / Co9S8, which is the distribution ratio diagram of elements in MXene@NiCo-LDH / Co9S8; (hi) is the transmission electron microscope (TEM) and HRTEM images of MXene@NiCo-LDH / Co9S8. It can be seen from the transmission electron microscope image of MXene@NiCo-LDH / Co9S8 that the hollow structure of NiCo-LDH / Co9S8 is completely wrapped by MXene nanosheets, indicating that they have good contact.
[0030] Then, the electrode is prepared using the above electrode material; Finally, Hg / HgO and Pt electrodes were used as reference electrodes, and the obtained composite electrode material was used as the positive electrode. Activated carbon, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and then mixed with ethanol as a solvent and applied on a foamed Ni sheet to prepare a negative electrode.
[0031] Figure 3It is a diagram of the component advantages of the composite electrode material of the present invention. Compared with the comparative electrode material, the composite electrode material prepared by the present invention exhibits excellent charge storage capacity and good electrical conductivity; Figure 5 This is the electrochemical performance test diagram of MXene@NiCo-LDH / Co9S8 / / AC supercapacitor. The shape of the CV curve remains basically unchanged, indicating that it has good rate performance.
[0032] Embodiment 3: (1) Preparation of MXene dispersion: 3.0 g Ti3AlC2 powder was slowly added to 2.5 g lithium fluoride hydrochloric acid solution, stirred at 50 °C for 26 h, centrifuged and washed, and then the centrifuge was vacuum dried at 70 °C for 14 h. Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion, wherein the concentration of MXene is 5 mg / mL; (2) Preparation of Co-MOF: Prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, 20 ml of methanol, 1.2 g of Co(NO3)2·6H2O, and 2.0 g of 2-methylimidazole; Then, the two solutions were mixed and stirred evenly. After reacting for 26 hours, the obtained product was finally centrifuged and dried to obtain the polyhedral precursor Co-MOF for later use; (3) Preparation of MXene@Co-MOF composite membrane: First, the Co-MOF prepared in step (2) is added to the MXene dispersion prepared in step (1), and stirred evenly. The amount of Co-MOF used is 60 mg. The MXene@Co-MOF composite membrane is obtained by vacuum filtration and set aside. (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a solvent of deionized water and ethanol to prepare a solution. The amount of Ni(NO3)2·6H2O was 30 mg in 10 mL of deionized water and 20 mL of ethanol solvent. Then, the MXene@Co-MOF composite membrane prepared in step (3) was immersed therein and kept at room temperature for 26 h to obtain a MXene@NiCo-LDH composite membrane. (5) Preparation of MXene@NiCo-LDH / Co9S8: Prepare an ethanol solution of thioacetamide, 10 mL of ethanol and 20 mg of thioacetamide, then immerse the MXene@NiCo-LDH membrane prepared in step (4) in the solution and react at 130 °C for 3 h to obtain MXene@NiCo-LDH / Co9S8, which is the product supercapacitor composite electrode material.
[0033] Then, the electrode is prepared using the above electrode material; Finally, Hg / HgO and Pt electrodes were used as reference electrodes, and the obtained composite electrode material was used as the positive electrode. Activated carbon, acetylene black and polyvinylidene fluoride were mixed in a mass ratio of 8:1:1, and then mixed with ethanol as a solvent and applied on a foamed Ni sheet to prepare a negative electrode.
[0034] Comparative Example 1: This comparative example prepares a supercapacitor composite electrode material, and the steps are as follows: (1) Preparation of MXene dispersion: 2.0 g Ti3AlC2 powder was slowly added to 2.0 g lithium fluoride hydrochloric acid solution, stirred at 40 °C for 24 h, centrifuged and washed. The centrifuge was then vacuum dried at 60 °C for 12 h, and Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion, the concentration of MXene is 4.5 mg / mL; (2) Preparation of Co-MOF: Prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, 20 ml of methanol, 0.9 g of Co(NO3)2·6H2O, and 1.6 g of 2-methylimidazole; Then, the two solutions were mixed and stirred evenly. After reacting for 24 hours, the obtained product was finally centrifuged and dried to obtain the polyhedral precursor Co-MOF for later use; (3) Preparation of MXene@Co-MOF composite membrane: First, the Co-MOF prepared in step (2) was added to the MXene dispersion prepared in step (1), and stirred evenly. The amount of Co-MOF was 60 mg, and the MXene@Co-MOF composite membrane was obtained by vacuum filtration; This material was used as the electrode material of Comparative Example 1, and similarly, an electrode was prepared using this material as the electrode material.
[0035] Comparative Example 2: This comparative example is based on comparative example 1, and the following operations are performed: Ni(NO3)2·6H2O was added to a solvent of deionized water and ethanol to prepare a solution. In 10 mL of deionized water and 20 mL of ethanol solvent, the amount of Ni(NO3)2·6H2O was 20 mg. Then, the MXene@Co-MOF composite membrane prepared in step (3) was immersed therein and kept at room temperature for 24 h to obtain a MXene@NiCo-LDH composite membrane. This material was used as the electrode material of Comparative Example 2. Similarly, it was used as the electrode material to prepare an electrode.
[0036] Figure 4 It is a performance characterization diagram of the composite electrode material prepared by the present invention (Example 2). Compared with MXene@Co-MOF and MXene@NiCo-LDH, the minimum internal resistance of MXene@NiCo-LDH / Co9S8 means good conductivity. In addition, the spectral slope of MXene@NiCo-LDH / Co9S8 is significantly steeper, indicating that the diffusion resistance of the electrolyte is the smallest. These EIS results support the formation of the ternary MXene@NiCo-LDH / Co9S8 nanostructure, which provides better conductivity and ion diffusion; Figure 6 The test result diagram of Comparative Examples 1 and 2 of the present invention.
[0037] Finally, the performance of the electrodes of each embodiment and comparative example was tested. By performing performance tests on embodiments 1-3 and comparative examples 1-2, the specific performance data are as follows: At the same time, the electrode capacitances of Example 2, Comparative Example 1 and Comparative Example 2 under different conditions were tested separately, and the results are as follows: Electrochemical test conditions <![CDATA[1 A g -1 ]]> <![CDATA[2A g -1 ]]> <![CDATA[3 A g -1 ]]> <![CDATA[5 A g -1 ]]> <![CDATA[8 A g -1 ]]> <![CDATA[10 A g -1 ]]> Comparative Example 1 272.0 228.0 190.2 142.0 104.0 88.0 Comparative Example 2 586.0 522.8 477.0 418.0 353.6 318.0 Example 2 808.0 725.6 768.0 613.0 550.4 512.0 The above data tests were conducted on the best embodiment 2 and comparative examples 1 and 2.
[0038] The method of the present invention is obtained by compounding with thioacetamide on the basis of comparative example 2. Transition metal chalcogenides have the advantages of multiple oxidation states, good thermal stability and abundant electrochemical redox reaction sites; MXene is currently a hot research topic in energy storage applications by etching the MAX phase of the A layer (usually Al or Si). The presence of development channels in MXene promotes the embedding and transportation of metal ions and electrolytes, and has extraordinary conductivity. By combining MXene with other battery electrode materials, the synergistic effect of the two will achieve excellent energy, power density and stability. It can be clearly seen that the energy density of the embodiment is 96.3W•h•kg -1 Above, the electrode capacitance is greater than 807.0F•g -1 , both better than the ratio of 272.8F•g -1 The electrode capacitance.
[0039] It can be seen from the tests of various embodiments and comparative examples that: The performance of the electrode prepared by the method of the present invention is greatly superior to that of the intermediate material.
[0040] The energy density of each embodiment of the present invention reaches 96.3 W•h•kg -1 Above; 1 A g -1 The electrode capacitance under the condition reached 807 F •g -1 Impedance Rct (Ω) is above 12.3; Impedance R s (Ω) is above 0.75.
[0041] The energy density of Comparative Examples 1 and 2 only reached 33.7W•h•kg -1 and 44.6W•h•kg -1 ; 1 Ag -1 The electrode capacitance under the condition reached 807F •g -1 Impedance Rct (Ω) is above 16.7; Impedance R s (Ω) are all above 0.9.
[0042] The energy density of conventional supercapacitors is currently between 10 and 15 W•h•kg -1 ; 1 A g -1 The electrode capacitance under the condition is 100~150F •g -1 Above; and the supercapacitor impedance Rct (Ω) and impedance R s The specific value of (Ω) will vary due to different manufacturing processes and materials.
[0043] The larger the electrode capacitance, the smaller the impedance; the better the performance of the supercapacitor, the electrode capacitance of Comparative Example 2 is lower than that of the present invention, the impedance is higher than that of the present invention, and the performance is lower than that of the present invention.
[0044] Furthermore, when MXene@NiCo-LDH / Co9S8-based HSC devices were assembled, the -1 The energy density is 96.4W•h•kg -1 , with extremely high energy density, and after 9,000 cycles, the initial capacitance retention rate can still reach 70.26%, with excellent cycle performance.
[0045] The present invention mixes MXene@Co-MOF with thioacetamide to prepare a MXene@NiCo-LDH / Co9S8 composite electrode material. The electrode material of the best embodiment 2 has a current density of 1A•g -1When the capacitance is 808.0 F·g -1 Such electrochemical performance can be attributed to the fact that MXene@NiCo-LDH / Co9S8 has abundant mesopores and high electrochemical activity. The above comparison results fully demonstrate that the composite electrode material prepared by the preparation method of the present invention has excellent performance. The problem of low energy density and cycle stability of electrode materials is fully solved by the method of the present invention, which is attributed to the effect brought about by gradually preparing three different component structures through different steps in the preparation method of the present invention.
[0046] It is obvious to those skilled in the art that the above embodiments are not intended to be exhaustive or limit the embodiments to the specific precise forms disclosed. It is obvious to those skilled in the art that certain modifications, combinations and variations can be made based on the above teachings.
Claims
1. A method for preparing a supercapacitor composite electrode material, characterized in that: The preparation method specifically comprises the following steps: (1) Preparation of MXene dispersion: Ti3AlC2 was added to a hydrochloric acid solution of lithium fluoride, stirred at 30-50°C for 22-26 h, centrifuged and washed, and then the centrifuge was vacuum dried at 50-70°C for 10-14 h. Ti3AlC2 in lithium fluoride was etched with hydrochloric acid to synthesize Ti3C2T X MXene nanosheets, then adding the nanosheets into deionized water and stirring evenly to obtain a MXene dispersion; (2) Preparation of Co-MOF: First, prepare methanol solutions of Co(NO3)2·6H2O and 2-methylimidazole respectively, then mix and stir the two solutions evenly, react for 22-26 hours, and finally centrifuge and dry the obtained product to obtain the polyhedral precursor Co-MOF; (3) Preparation of MXene@Co-MOF composite membrane: adding the Co-MOF prepared in step (2) to the MXene dispersion prepared in step (1), stirring evenly, and preparing a MXene@Co-MOF composite membrane by vacuum filtration; (4) Preparation of MXene@NiCo-LDH: Ni(NO3)2·6H2O was added to a mixed solvent of deionized water and ethanol to prepare a solution, and then the MXene@Co-MOF composite membrane prepared in step (3) was immersed in the solution and kept at room temperature for 22 to 26 hours to obtain a MXene@NiCo-LDH membrane; (5) Preparation of MXene@NiCo-LDH / Co9S8: Prepare an ethanol solution of thioacetamide, and then immerse the MXene@NiCo-LDH membrane prepared in step (4) in the solution, and react at 110-130°C for 1-3h to obtain MXene@NiCoLDH / Co9S8, which is the product supercapacitor composite electrode material.
2. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that: In the hydrochloric acid solution of lithium fluoride in step (1), the mass concentration of lithium fluoride is 10-30 mg / ml.
3. The method for preparing a supercapacitor composite electrode material according to claim 1 or 2, characterized in that: In the step (1), the amount of Ti3AlC2 added to every 100 ml of lithium fluoride hydrochloric acid solution is 1.0-3.0 g.
4. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that: The concentration of the MXene dispersion in step (1) is 4-5 mg / ml.
5. The method for preparing a supercapacitor composite electrode material according to claim 3, characterized in that: In the step (2), the two methanol solutions are mixed in a volume ratio of 1:1, and in every 20 ml of methanol, the amount of Co(NO3)2·6H2O is 0.7-1.1 g, and the amount of 2-methylimidazole is 1.1-2.1 g.
6. The method for preparing a supercapacitor composite electrode material according to claim 1 or 4, characterized in that: In the step (3), the amount of Co-MOF used in every 10 ml of MXene dispersion is 40-60 mg.
7. The method for preparing a supercapacitor composite electrode material according to claim 1, characterized in that: In the step (4), the ratio of deionized water to ethanol is 1:2, and the amount of Ni(NO3)2·6H2O used in every 30 ml of the mixed solvent is 10-30 mg.
8. The method for preparing a supercapacitor composite electrode material according to claim 6, characterized in that: The ethanol solution of thioacetamide in step (5) has an amount of 10-20 mg of thioacetamide per 10 ml of ethanol.
9. A supercapacitor composite electrode material, characterized in that: The composite electrode material is prepared by the preparation method described in any one of claims 1 to 8.
10. An electrode system for a supercapacitor, characterized in that: The composite electrode material of claim 9 is used as the positive electrode; the negative electrode is prepared by mixing activated carbon, acetylene black and polyvinylidene fluoride, then mixing with ethanol as a solvent, and applying it on a foamed Ni sheet.
Citation Information
Cited By
Preparation method of transition metal oxide / sulfide electrode material and supercapacitor
CN121839445A